2013
DOI: 10.1021/bi400643s
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of More Potent Alternatives to HAMLET, a Tumoricidal Complex of α-Lactalbumin and Oleic Acid

Abstract: HAMLET is a complex of human α-lactalbumin (hLA) with oleic acid (OA) that kills various tumor cells and strains of Streptococcus pneumoniae. More potent protein-OA complexes were previously reported for bovine α-lactalbumin (bLA) and β-lactoglobulin (bLG), and pike parvalbumin (pPA), and here we explore their structural features. The concentration dependencies of the tryptophan fluorescence of hLA, bLA, and bLG complexes with OA reveal their disintegration at protein concentrations below the micromolar level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Earlier, we have shown that OA binding shifts the distribution of oligomeric forms of hLA, bovine α‐lactalbumin, bovine β‐lactoglobulin, and PA toward higher order oligomers . Since formation of the cytotoxic oligomers of IDPs plays an important role in pathogenesis of some human diseases, we have examined the OA/LA‐induced changes in the quaternary structure of the chosen proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we have shown that OA binding shifts the distribution of oligomeric forms of hLA, bovine α‐lactalbumin, bovine β‐lactoglobulin, and PA toward higher order oligomers . Since formation of the cytotoxic oligomers of IDPs plays an important role in pathogenesis of some human diseases, we have examined the OA/LA‐induced changes in the quaternary structure of the chosen proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, the aforementioned complexes of bovine α-LA, bovine β-lactoglobulin, and pike parvalbumin with oleic acid were more potent against various tumor cells and strains of Streptococcus pneumonia than the original HAMLET complex. Subsequent biophysical analysis revealed that although the HAMLET-like complexes were characterized by marked structural differences, all of them exhibited a common feature, where the association of proteins with oleic acid resulted in a shift of the distribution of their oligomeric forms toward higher-order oligomers [ 297 ]. In addition to these proteins, lactoferrin also can form HAMLET-like complexes with oleic acid, which induce apoptosis in tumor cells through both death receptor- and mitochondrial-mediated pathways [ 298 ].…”
Section: Anti-tumorigenic Activities Of α-Lactalbuminmentioning
confidence: 99%
“…UDG "melts" ds d(pN) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] partially and contacts with both chains of such relatively short ODNs almost independently [37,50]. In contrast, DNA polymerases [30,31], AP endonuclease [33], Topo I [39,40], 8-oxoguanine-DNA glycosylases [34,38] interact with both basepaired DNA strands.…”
Section: Affinity Of La For Dna Duplexesmentioning
confidence: 99%
“…This cofactor was identified as a specific fatty oleic acid [9]. It has been found that α-LA may be not the main cytotoxic component of its complexes with oleic acid, but the acid is more important [10,11].…”
Section: Introductionmentioning
confidence: 99%